Beiträge zu einer Geographie des Fremdenverkehrs - Christaller, Walter (ERDKUNDE, 1955)
As the proper principle for a systematic subdivision of the field of economic geography the place occupied by any one type of economic activity within the spatial framework of functional relationships should be used rather than the respective economic activities themselves. Thus only one kind of economic activity is connected in a typical way with the periphery of the area of human occupance namely, the tourist trade. To demonstrate this is the task of a geography of the tourist trade. A geography of the tourist trade can be further subdivided according to the location of its activity. The localisation factors are: attractions of climate and landscape, possibilities for the pursuit of sports, springs with therapeutic qualities, art treasures and antiquities, historical or cultural sights, economic specialities and peculiarities. In the historical development of modern tourist trade five periods can be distinguished. The first lasted from about 1790 to 1840 until the beginning of the means of mass transport, steamship and railway. The first travel guide books were published between 1830 and 1840. The second period, which lasted until 1870, forms a parallel to the stage of cottage-industry in the sector of manufacturing. The third period from 1870 to 1900 is characterized by the commencement of a special industry catering for tourists. Travelling, however, became only a mass phenomenon in the fourth period, after 1900, in which sport activities, and in particular winter sports, came more and more to the forefront. Since 1930 we have been in the fifth period during which on the one hand conducted group travel, organized by agencies, and on the other, a trend to the periphery, are typical features. The destinations of tourists are very much subject to the influence of changes in fashion. As a typical case, one might cite the discovery by some painters of an attractive corner, untouched by modern civilization, which in consequence soon becomes fashionable and finally becomes the common goal of many group journeys. The connoisseurtraveller has in the meantime discovered and visited new places which, however, are bound to suffer the same fate. In order to elucidate the spatial interrelations an investigation of the countries and places of origin of the tourists is of importance. The average length of sojourn of the guests is a suitable basis for the classification of tourist resorts. These points are illustrated by a number of examples. In the example of the Wallis (Valais) in particular, the altitudinal grading of the tourist trade establishments is discussed; here the conquest of the heights is a special case of the trend to the periphery. In the case of Jutland, on the other hand, the bathing beaches, also areas of a typical peripheral kind, emerge as particularly important. The example of Sicily shows that there, tourist trade has barely entered its fourth period. Nevertheless even in Sicily tourist trade areas of considerable extent with isolated mountain hotels and camping grounds have recently begun to develop.